The Phenomenology of a Railway Expedition in China: The Gate, the Station, the Journey and the Arrival - Junjie Xi; Paco Mejias Villatoro (Ambiances)
Hosting more than two-thirds of the global high-speed train network, and growing at an unprecedented rate, China has become an interesting location for studying this infrastructure. In this paper, the authors begin by introducing some particularities related to the high-speed travel experience, in order to provide a general understanding of how it affects people’s perceptions of time and space. This is followed by an explanation of some peculiarities that have defined the Chinese case as unique. Grounded on theories that assert the interlaced connection between modernity and phenomenology, in this paper the authors explore the connection between the conditions that defined modernity in China and the phenomenology of travel using high-speed trains. The problematic initial approach to Chinese modernity – through the Great Leap Forward and the Cultural Revolution – impacted later decisions regarding the new infrastructure, rendering high-speed train journeys in China unique. After the end of the Cultural Revolution in 1976, when China recovered a sense of normality and togetherness, modernity was globally staged out. Two years later, China commenced the development of its high-speed rail (HSR) network and the beginning of the reform era, as part of its statements of a reframed modernity. This paper explores how the singularities of the Chinese modernity have affected the development of the High-speed train network, defining a particular phenomenology of the trip.